KNOWLEDGE OF THE NEW SOCIETY AND CULTURE OF THE LAO GOVERNMENT IN A REIMAGINED ERA THROUGH PRINTED MATERIALS - Panyavuttrakul, Wasin (Journal of Social Science and Cultural, 2023)
Research studies by historical method On the creation of a new Lao society and culture of the Lao PDR government after the New Imagination Policy Which is quite a guideline that is both consistent with and contradicts with the old guidelines that the Party and the Lao PDR government have implemented during the years 1975 - 1985, which may reflect the creation of people new socialism In the new society and culture of Laos under the guidance of the true Lao socialist state And not under the shadow of a model socialist country like the Soviet Union. or neighboring countries like China and Vietnam But if it is a Lao socialist state based on the true Lao social context The researcher will look through various publications of the Lao People's Revolutionary Party. and the Home Front Organization (Alliance), which is an important mouthpiece in creating a new society and culture of the Lao PDR government, such as newspapers and various documents from the Lao People's Revolutionary Party and the Lao PDR government. It is another important way to disseminate the way to create a new Lao society and culture from the government to the people. The study found that Creation of knowledge about the new society and culture of the Lao government in a reimagined era through print media. Before the promulgation of the New Imagination Policy, it was divided into 2 phases: Phase 1 was before 1986, creating a set of knowledge related to the new cultural society of Lao PDR in the past. Re-imagining from Lao Government Publications Phase 2 is after 1986. It creates a set of knowledge relating to the new cultural society of Lao PDR in the post-reimagined era from Lao government publications.